THE RELATIONSHIP BETWEEN PARENT INVOLVEMENT AND LEARNING ACHIEVEMENT IN STUDENTS - Novita Maulidya Jalal (International Research of Multidisciplinary Analysis, 2023)
This research is based on the many problems of adolescent students in being involved in the learning process at school. The purpose of this study is to determine the relationship between parent involvement and student engagement. This research was conducted using a library research approach. The research subject is the journal of the results of previous research related to the variables studied. Data collection was carried out using a literature review. Based on the results of this study it is known that there is a relationship between parental involvement and student achievement. Based on the results of a review of 9 research journals, it is known that parental involvement can affect increased learning motivation which can improve student learning achievement for the better. This is because there is encouragement from parents towards children so that it creates great enthusiasm embedded in children to learn and achieve achievements, the role of parents is very important in the development of children's education, they will understand the achievement of learning activities that they carry out to achieve optimal learning achievements